Introduction to the electron theory of metals - Mizutani, Uichirō (Cambridge University Press, 2001)
Using an accessible approach that compares theory and experiment as much as possible, this textbook gives a complete account of the theory of electrons in metals from the basics of one-electron band theory to topics of current research such as superconductors and quasicrystals.